Green Economy Analysis in Hospital Management to Improve Sustainability and Operational Efficiency - Rendi Randika; Ahmad Redho; Yoana Agnesia (Indonesian Journal of Global Health Research, 2025)
The Green Economy concept in the healthcare sector is an important strategy to improve the sustainability and efficiency of hospital operations. As institutions that operate 24 hours a day, hospitals consume significant amounts of energy and produce medical and non-medical waste that can impact the environment if not managed properly. This study aims to analyze the implementation of Green Economy principles at Bina Kasih Hospital in Pekanbaru, focusing on three main policy instruments: energy efficiency, waste management, and service digitalization systems, and their relationship to improving hospital operational efficiency and sustainability. This study used a mixed method with a quantitative and qualitative design to obtain a comprehensive picture. Quantitative data were obtained from 40 respondents who were purposively selected using a standardized questionnaire. The validity test results showed that all question items had a calculated r value > 0.444 (with 20 samples), thus being declared valid. Meanwhile, the reliability test results using Cronbach's Alpha were 0.906, indicating an excellent level of internal consistency (higher than the minimum limit of 0.60). Qualitative data were collected through in-depth interviews and focus group discussions (FGDs) with key stakeholders in the hospital environment. Data analysis was conducted using univariate, bivariate (Chi-square test), and multivariate (logistic regression) analyses for quantitative data, as well as SWOT analysis and Cost-Benefit Analysis to strengthen the qualitative findings. The results showed that the digitalization system had the strongest influence on operational efficiency (p=0.001; PR=2.754), followed by waste management (p=0.023; PR=2.056) and energy efficiency policies (p=0.045; PR=1.821). Key challenges include limited infrastructure, inconsistent policy enforcement, and low employee awareness. However, the implementation of Green Economy strategies has been shown to improve cost efficiency, strengthen the institution's reputation, and support environmental sustainability.